THE IMPACT OF E-LEARNING ON UNIVERSITY STUDENTS’ ACADEMIC ACHIEVEMENT AND CREATIVITY - zare, Mohammad; Sarikhani, Rahele; Salari, Mostafa; Mansouri, Vahid (Journal of Technical Education and Training, 2016)
Research on the efficacy of ICT-based teaching methods in improving generic skills in addition to content skills among future workforce is increasing. Â Accordingly, this study investigates the impact of e-learning on creativity and content knowledge of chemistry students at the Payame Noor University of Hamedan, Iran. The study used the pre-test/post-test experimental design with a control group. The statistical population of the study included was 100 pure chemistry students who were following two separate classes. Forty students were selected from this group who placed in the experimental group (n = 20) and the control group (n = 20). Two instruments were used for data collection; a specifically developed test on the Introduction to Chemistry course and the Abedi Inventory for assessing creativity. Results of data analysis using the independent t-test (aided by SPSS) demonstrated statistically significantly higher scores for the experimental group on measured variables, knowledge and creativity. Therefore, it is concluded that e-learning is effective for knowledge and creativity acquisitions among chemistry students and the greater e-learning opportunities should be provided for wider audiences.